Invasive cancers are not necessarily from preformed in situ tumours — an alternative way of carcinogenesis from misplaced stem cells. Issue 7 (7th June 2013) - Wang, Rui‐An; Li, Zeng‐Shan; Zhang, Hui‐Zhong; Zheng, Ping‐Ju; Li, Qin‐Long; Shi, Jian‐Guo; Yan, Qing‐Guo; Ye, Jing; Wang, Jing‐Bo; Guo, Ying; Huang, Xiao‐Feng; Yu, Ying‐Hao
Abstract Cancers are thought to be the result of accumulated gene mutations in cells. Carcinomas, which are cancers arising from epithelial tissues usually go through several stages of development: atypical hyperplasia, carcinoma in situ and then invasive carcinoma, which might further metastasize. However, we think that the present pathological data are enough to prove that there might be an alternative way of carcinogenesis. We propose that majority of invasive cancers arise in the connective tissue stroma de novo, from the misplaced epithelial stem cells which come to the wrong land of connective tissue stroma by accident. The in situ carcinomas, which are mostly curable, should not be considered genuine cancer, but rather as quasi‐cancer. We design this new theory of carcinogenesis as the stem cell misplacement theory (SCMT). Our SCMT theory chains together other carcinogenesis theories such as the inflammation‐cancer chain, the stem cell theory and the tissue organization field theory. However, we deny the pathway of somatic mutation theory as the major pathway of carcinogenesis.